2020
DOI: 10.1002/cjce.23749
|View full text |Cite
|
Sign up to set email alerts
|

Experimental methods in chemical engineering: Rheometry

Abstract: Rheometry is an experimental technique that measures the relationship between stresses, strains, and their derivatives of fluids and deformable materials. Capillary and Couette viscometers were among the first instruments used to study rheology but now sophisticated shear and extensional rheometers are widely available for quality control, research, and product development. Here, we introduce the basics of rheology, define material functions, and describe conventional instruments, physical principles, applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…57 Hence, according to contour plot in Fig. 5(a2), catalyst dosage and concentration show prominent interaction on removal efficiency of BPA, which is in good agreement with statistically signicant result in Table 2 and large magnitude of term AB in eqn (3). As shown in two gures ( Fig.…”
Section: Response Surface Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…57 Hence, according to contour plot in Fig. 5(a2), catalyst dosage and concentration show prominent interaction on removal efficiency of BPA, which is in good agreement with statistically signicant result in Table 2 and large magnitude of term AB in eqn (3). As shown in two gures ( Fig.…”
Section: Response Surface Analysissupporting
confidence: 75%
“…Hence, BPA has been detected in various environmental media, including municipal wastewaters, sewage, surface water, landlls and so on. 3,4 Moreover, previous experimental and epidemiological studies 5,6 have shown that BPA had the potential to affect the endocrine system through disturbing the synthesis, transport and metabolism of estrogenic and thyroid hormones. BPA has caused great concern due to its widespread application and large production.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low aspect ratio fibers are more easily aligned along the direction of flow than those having a higher aspect ratio, causing less restriction on the flowability of the composite. [38][39][40] HDTs of the neat TPO matrix and its glass fiber reinforced composites were obtained under a load of 0.455 MPa and are presented in Figure 8. HDT measurements were performed to investigate short-term heat resistance of the samples and investigate the maximum temperature at which polymer can be used as a rigid material.…”
Section: F I G U R E 3 Glass Fiber Length Dispersion For Thermoplastimentioning
confidence: 99%
“…This enhancement of HDT in the composite system could be due to the improvement of modulus, the reduction of high‐temperature creep, and restricted relaxation of macromolecules in the presence of fillers at high temperatures. [ 2,37,38 ]…”
Section: Resultsmentioning
confidence: 99%